Coproductive Imaginaries for Climate Change Adaptation: A Case of Adaptation Initiatives in the Gandaki River Basin, Western Nepal. Issue 2 (4th March 2023) - Ghimire, Rajiv; Chhetri, Netra
Abstract : For too long climate change adaptation was taken as a problem to be addressed through technological fixes. Using a place-based and contextual approach to imaginaries, we present emerging dialectics that collectively bring a set of knowledge to address climate adaptation challenges. With the analysis of the Local Adaptation Plans of Action (LAPA) initiative in the Gandaki River Basin, Western Nepal, we explore how local adaptation initiatives promote sociotechnical imaginaries and how it translates to social practice. Drawing on an initial field visit, stakeholder interviews, a scoping review, and the analysis of LAPA documents, this article reveals that local adaptation practices not only are designed to address climatic challenges but are also a response to a host of other ongoing stresses and are firmly connected to local communities. Although the LAPA initiative in Nepal looks innovative, there still is a need to reinforce grassroots-level initiatives and practices with the use of both traditional and modern knowledge and capacity to enhance the adaptation action at the local level. The study of Nepal's LAPA shows how both scientific and traditional knowledge coalesce at the community level as a response to changing climate, illustrating the complex and hybrid nature of climate adaptation.